(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Over the past several decades, the structure, size, and dynamics of families have undergone substantial transformations, marking a significant shift in societal norms and demographic patterns. This evolution is particularly pronounced in the context of shrinking family sizes, which can be attributed to a noticeable decline in marriage rates, an increase in divorce rates, and a reduced birth rate. Furthermore, the demographic landscape is being reshaped by the dual phenomena of migration and an aging population, trends that are mirrored within Macedonian society as well.The latest population census in the Republic of North Macedonia, conducted in 2021 after a hiatus of twenty years since the 2002 census, provides invaluable data for understanding these demographic shifts. This research aims to delve into and compare the data from these two pivotal years to examine the evolution of family structures in Macedonia over this period. By employing quantitative analysis techniques and a descriptive research approach, including content analysis, the study aims to paint a detailed picture of how Macedonian families have changed.The findings reveal significant changes in the demographic composition of households and families, with migration and an aging population being key drivers of this transformation. The study uncovers a trend towards smaller, more diverse family units, highlighting the long-term shifts in family structures and demographics. This comprehensive analysis not only captures the immediate changes but also sheds light on the broader, long-term trends affecting Macedonian families, contributing to our understanding of societal changes and family dynamics.